Study of Antigravity in an F(R) Model and in Brans-Dicke Theory with Cosmological Constant. (14th August 2014) - Oikonomou, V. K.; Karagiannakis, N.
Abstract : We study antigravity, that is, having an effective gravitational constant with a negative sign, in scalar-tensor theories originating from F ( R ) theory and in a Brans-Dicke model with cosmological constant. For the F ( R ) theory case, we obtain the antigravity scalar-tensor theory in the Jordan frame by using a variant of the Lagrange multipliers method and we numerically study the time dependent effective gravitational constant. As we will demonstrate by using a specific F ( R ) model, although there is no antigravity in the initial model, it might occur or not in the scalar-tensor counterpart, mainly depending on the parameter that characterizes antigravity. Similar results hold true in the Brans-Dicke model.